Learning Lives and Reconstructing Identities of young adult North Korean defectors - Hyewon Park Park (Adult Education Research Conference, 2017)
This study is to explore young adult North Korean defectors’ learning and identity reconstruction process within daily activities in South Korea based on Cultural-historical activity theory as a theoretical framework.
Keywords: Young adult North Korean defectors; Identity reconstruction; Cultural-historical activity theory